The Effectiveness of the Active Recall Strategy and the Unique Path Strategy in Acquiring Social Concepts among Fifth-Grade Female Pupils and Their Vivid Memory - Hussein Oleiwi, Asraa ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
The study aimed to identify the effectiveness of the Active Recall Strategy and the Unique Path Strategy in acquiring social concepts and developing vivid memory among fifth-grade female pupils. The researcher adopted a quasi-experimental design with partial control, employing two post-tests. The research sample consisted of (102) female pupils from Al-Yara’ Primary School for Girls, who were randomly assigned into three groups: two experimental groups and one control group. The researcher taught the three groups herself according to the prescribed curriculum for the first semester of the academic year (2025–2026). Two instruments were prepared: a social concepts acquisition test and a vivid memory test, whose validity and reliability were verified. The results revealed the superiority of the two experimental groups over the control group, leading to a set of educational recommendations and suggestions presented in Chapter Four. DOI: https://doi.org/10.54633/2333-024-057-016